Comparing the effects of swimming among male and female elite athletes on bone mineral density acquisition - Khaledi, A.; Imeri, B.; Gheitasi, M.; Mirmoezzi, M. (Asian Journal of Sports Medicine, 2023)
Background: Despite the many therapeutic benefits of swimming, there is still conflicting evidence about its benefits for bone health and osteoporosis prevention, especially in elite swimmers according to their sex. It is known that sex differences can affect the acquisition of minerals by the bone.